Artificial Intelligence Similarity Index Detection App as an Anti-Plagiarism Campaign Against Intellectual Property Crime - Wahyudi, M Iman; Sa’idu, Sabo Jamilu (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2023)
This paper aims to discuss plagiarism according to Indonesian and Islamic laws and develop applicable solutions for detecting similarity index plagiarism. Plagiarism is the act of taking someone else’s work and claiming it as theirs without giving recognition or credit to the original owner. This practice is against positive and Islamic laws. The method used in this paper is RAD (Rapid Application Development), one of the software development methods that emphasises the speed and flexibility of the results of the trials. We found that this application could detect the similarity index of a text composed by an AI tool like ChatGPT. This application can be implemented in education but still has limitations. This application cannot detect plagiarism from sources unlisted in the database. Therefore, further research must address this problem.